RESPONSIBILITY AS AN IMPORTANT INDICATOR EDUCATION OF THE CHILD'S PERSONALITY (Pedagogy of Higher and Secondary Education, 2007)
The notion of the responsibility of the personis opened in the article, peculiarities of its development in preschool age is considered; the main features of definitions of responsibility of children in preschool age are found.